Green Transformation in a Special Economic Zone. A Case Study of Krakow Technology Park - Maroń, Jolanta (Publishing House of Wroclaw University of Economics and Business, 2025)
The chapter discusses green transformation in a special economic zone, using Krakow Technology Park (KTP) as a case study. It presents the role of technology parks in fostering innovation and sustainable development, and describes KTP’s ecological initiatives, including incubation programmes, R&D projects, green infrastructure development, and Smart City activities. Attention is given to KTP’s cooperation with businesses, universities, and international organisations. The conclusions highlight KTP’s significance as a leader in green transformation and a model for other zones in Poland.
Quote as: Maroń, J. (2025). Green Transformation in a Special Economic Zone. A Case Study of Krakow Technology Park. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 240-‑247). Publishing House of Wroclaw University of Economics and Business.
Keywords: green transformation; technology park; sustainable development; ecological innovations; special economic zone